O setor sucroalcooleiro no Pontal do Paranapanema: uma análise a partir do licenciamento ambiental - Rezende, Wallace Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The development of the sugar and alcohol sector and its sugar cane cultivation has been given in an accelerated way in Pontal do Paranapanema, mainly from the last decade, and with this has taken quick changes in the dynamic socio-economic and environmental of the region, further accentuating some conflicts and dilemmas social and environmental legacy. This work was done in order that these issues are further explored, that of moving towards a greater theoretical-scientific maturity, and even has a better apparatus to support measures (corrective or preventive) that show required anti such conflicts. For this purpose, we used the environmental licensing as a means of doing this analysis, since it is one of the main instruments of control/ regulation of the State against the development of activities of the sugar and alcohol sector. We also used a little of the vast potential of information that is contained in the environmental agencies. In this case, we used six Environmental Impact Study / Environmental Impact Report (EIS /EIR), six Preliminary Environmental Reports(PER), five Characterization of Enterprise Memorials (CEM), among other documents /studies present there. Some of the information, organized and made available in this work, has even greater potential to be exploited. It was also made an essential literature survey and of the laws related to licensing and alcohol and sugar sector

O desenvolvimento do setor sucroalcooleiro e da cultura da cana-de-açúcar tem se dado de maneira acelerada no Pontal do Paranapanema, principalmente a partir da última década, e com isto, tem decorrido súbitas mudanças na dinâmica sócio-econômico-ambiental da região, acentuando ainda mais alguns conflitos e impasses sociais e ambientais preexistentes. Este trabalho foi elaborado a fim de que tais questões sejam mais bem analisadas, que se caminhe para um maior amadurecimento teórico-científico e, inclusive, se tenha um melhor aparato para fundamentar medidas (corretivas ou preventivas) que se mostrem necessárias anti tais conflitos. Para tanto, utilizou-se do licenciamento ambiental como um dos meios de se fazer tal análise, já que é um dos principais instrumentos de controle/regulação do Estado frente ao desenvolvimento das atividades do setor sucroalcooleiro. Também se utilizou de um pouquinho do vasto potencial de informações que estão contidas nos órgãos ambientais. Neste caso, foram utilizados seis Estudos de Impacto Ambiental/Relatórios de Impacto Ambiental (EIAs/RIMAs), seis Relatórios Ambientais Preliminares (RAPs), cinco Memoriais de Caracterização dos Empreendimentos (MCEs), entre outros documentos/estudos ali presentes. Algumas das informações, organizadas e disponibilizadas neste trabalho, tem inclusive, um maior potencial de serem exploradas. Foi feito também um imprescindível levantamento bibliográfico e das legislações correlacionadas ao licenciamento e ao setor sucroalcooleiro
Keywords: Engenharia ambiental; Política ambiental; Impacto ambiental; Cana-de-açúcar - Paranapanema, Pontal do (SP)